2010
DOI: 10.1080/00140130903581631
|View full text |Cite
|
Sign up to set email alerts
|

Six-degree-of-freedom whole-body vibration exposure levels during routine skidder operations

Abstract: This research focuses on quantifying six-degree-of-freedom (6-DOF) whole-body vibration (WBV) exposure levels that occur in Northern Ontario skidders during routine field operating tasks. 6-DOF vibration running root-mean-square (RMS) acceleration levels at the operator/seat interface were determined for eight skidders while driving loaded, driving unloaded, picking up a load, dropping off a load and ploughing logs under field operating conditions. The acceleration data were weighted in accordance with ISO 263… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In seated vehicles such as forklifts, seat suspension type also has a significant impact on WBV exposure (Blood et al 2010). Whole-body vibration assessments on many different machinery types have revealed vibration exposures that exceed ISO standards for health or comfort, such as in all terrain vehicles (Milosavljevic et al 2010), forklifts (Hoy et al 2005), and skidders (Jack et al 2010); however no studies could be found evaluating WBV exposure in machines operated while standing, such as the sulky.…”
Section: Introductionmentioning
confidence: 98%
“…In seated vehicles such as forklifts, seat suspension type also has a significant impact on WBV exposure (Blood et al 2010). Whole-body vibration assessments on many different machinery types have revealed vibration exposures that exceed ISO standards for health or comfort, such as in all terrain vehicles (Milosavljevic et al 2010), forklifts (Hoy et al 2005), and skidders (Jack et al 2010); however no studies could be found evaluating WBV exposure in machines operated while standing, such as the sulky.…”
Section: Introductionmentioning
confidence: 98%
“…Vehicle tasks coupled with a description of the routes traveled can be found in Table 1. Pot hauler vibration data were further separated into pot banging, driving loaded and unloaded because of the differences in WBV between the tasks as determined by previous studies [21,22]. Each vehicle was selected for the study based on operator complaints of large vibrations, an increased level of workplace injuries, high operator turnover rate as well as vehicle availability.…”
Section: Methodology 21 Vehicle Descriptionsmentioning
confidence: 99%
“…To date, WBV data has been collected on locomotives [17,18], garbage [19] and transport trucks [11,20], as well as military [10] forestry [14,[21][22][23] and mining [24] vehicles. However, no 6DOF vibration data has been recorded on mobile machines within the steel making industry.…”
Section: Introductionmentioning
confidence: 99%
“…These risks are evident in epidemiological studies that report an increased risk of low back pain, and degenerative changes to the spinal column [6,7]. Certain industries, notably mining, construction, steel making and forestry, involve high levels of vibration [8][9][10][11][12][13][14][15][16][17][18], including complex 6 degree of freedom (df) vibration [17,19].…”
Section: Introductionmentioning
confidence: 99%